GRAMSCI AND SAVIANI: EDUCATION AS AN INSTRUMENT OF SOCIAL TRANSFORMATION IN THE MARXIST PERSPECTIVE - Elias Garcia, Tatiane (Revista Gênero e Interdisciplinaridade, 2024)
This article explores the contributions of Antonio Gramsci and Dermeval Saviani to the critical theory of education, highlighting its distinct views on the role of education in social transformation. While Gramsci emphasizes cultural hegemony and the formation of organic intellectuals, Saviani develops historical-critical pedagogy, focusing on concrete educational practice and material conditions of education in Latin America. This study investigates the theoretical contributions of Antonio Gramsci and Dermeval Saviani to education, exploring its complementary and distinct perspectives on how education can be an instrument of social transformation. Gramsci, influenced by Western Marxism, highlights cultural hegemony and the formation of organic intellectuals as strategies to challenge the ideological domination of the ruling classes. In contrast, Saviani, with his historical-critical pedagogy, focuses on concrete educational practice and educational policies, especially in the Latin American context, proposing an education that promotes critical awareness and the emancipation of the oppressed.